The Government Communication Strategy through Social Media to Increase Public Awareness - Jamalullail, Jamalullail; Safira, Fidan; Hamdi, Hamdi (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2023)
Public communication for the government is crucial to establish interaction and build public trust. This study aims to identify the goals and forms of government communication strategies using social media. This research uses the SLNA (Systematic Literature Network Analysis) method with limitations on emerald and science direct data sources published in the 2018-2022 range. Network Analysis is used to map keywords from selected articles to find theme patterns. The findings of this study indicate that the government uses social media not always to show reputation or transparency, but rather to socialize to increase awareness and interaction. However, the impact of using social media shows more community participation than awareness.Keywords: Public communications, government, social media, awareness, participation ABSTRAKKomunikasi publik bagi pemerintah menjadi hal krusial untuk menjalin interaksi dan membangun kepercayaan masyarakat. Penelitian ini bertujuan untuk mengidentifikasi tujuan dan bentuk strategi komunikasi pemerintah melalui pemanfaatan media sosial. Penelitian ini menggunakan metode SLNA (Systematic Literature Network Analysis) dengan batasan pada sumber data emerald dan science direct yang terbit rentang tahun 2018-2022. Network Analysis digunakan untuk memetakan kata kunci dari artikel terseleksi guna menemukan pola tema. Temuan penelitian ini menunjukkan bahwa tujuan pemerintah memanfaatkan media sosial tidak selalu untuk menunjukkan reputasi atau transparansi, namun lebih kepada sosialisasi untuk menumbuhkan awareness dan interaksi. Namun, dampak dari pemanfaatan media sosial lebih banyak menunjukkan adanya partisipasi masyarakat dari pada awareness.Kata Kunci: Komunikasi publik, pemerintah, media sosial, awareness, partisipasi